Propuesta para el diseño de un plan de gestión turística en la comunidad Fakcha Llakta en el cantón Otavalo - Guevara García, Alisson Habsleidy (2022)
The Fakcha Llakta community is a village of Kichwa origin located in the town of Peguche. Its main activity is tourism, which allows tourists to learn about the daily life of the community through different activities such as gastronomy and handicrafts. This study proposes to determine the current situation of the tourist activity in the sector through the collection of information from the inhabitants of the Peguche sector, and in turn from the representatives of the Fakcha Llakta community. In this way, we seek to implement the methodology for a tourism management model in the community, which will allow for a better tourism and community organization. With the purpose that in the future, with the help of a public entity, this methodology can be taken into account for the implementation of a tourism management plan. The methodology applied in this research is aligned with the descriptive - analytical, synthetic and deductive research methods, of equal importance three research techniques are applied: the survey, the interview and the observation\; we worked with a non-probabilistic sample, which was applied to 100 people belonging to the Peguche sector. The results gathered information on the lack of community organization and tourism management, such as the lack of promotion, improvement of services and lack of training on the part of the community members. It was concluded that this is due to lack of knowledge and lack of support from public entities\; however, the community has managed to continue with this activity to generate more benefits and at the same time to conserve and protect the Peguche waterfall Protected Forest with their efforts and the income they receive from the entrance fee to the forest.